ANALISIS PERGUB BALI NOMOR 2 TAHUN 2024 DENGAN MODEL TEORI KRITIS - Widiastuti, Rika; Noak , Piers Andreas; Erviantono , Tedi (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
This research analyzes Bali Governor Regulation number 2 of 2024, which regulates the procedures for paying fees for foreign tourists, using a Critical Theory approach. The focus of the research is to identify the social, economic and environmental impacts of this regulation on the main tourism destination, Bali. The analysis covers key aspects of the Governor Regulations, evaluating potential inequalities and social conflicts that may arise. In addition, the research discusses the impact of levy payment procedures on the participation and contribution of foreign tourists, as well as policy implications for local communities and the environment. With a critical approach, this research aims to provide in-depth insights and recommendations for more inclusive and sustainable policies.